Bilingual and monolingual children prefer native-accented speakers - Souza, Andre L.; Byers-Heinlein, Krista; Poulin-Dubois, Diane (Frontiers in Psychology, 2013)
Adults and young children prefer to affiliate with some individuals rather than others. Studies have shown that monolingual children show in-group biases for individuals who speak their native language without a foreign accent (Kinzler et al., 2007). Some studies have suggested that bilingual children are less influenced than monolinguals by language variety when attributing personality traits to different speakers (Anisfeld and Lambert, 1964), which could indicate that bilinguals have fewer in-group biases and perhaps greater social flexibility. However, no previous studies have compared monolingual and bilingual children's reactions to speakers with unfamiliar foreign accents. In the present study, we investigated the social preferences of 5-year-old English and French monolinguals and English-French bilinguals. Contrary to our predictions, both monolingual and bilingual preschoolers preferred to be friends with native-accented speakers over speakers who spoke their dominant language with an unfamiliar foreign accent. This result suggests that both monolingual and bilingual children have strong preferences for in-group members who use a familiar language variety, and that bilingualism does not lead to generalized social flexibility.